The Use of Crossword Media to Improve Mufrodat Learning Outcomes in Arabic Language Learning - Wiwaha, Rizzaldy Satria; Fauzi, Safran; Syafitri, Rima Amalia; Wahyudin, Dedih (Kalamuna: Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2024)
This article discusses Arabic Language Learning (mufrodat) in class VIII students of Mts Minhajul Haq Purwakarta by using Crossword media because the learning outcomes of mufrodat in Arabic language learning in general students' scores still have not reached the Minimum Completeness Criteria (KKM), this is because the Arabic language learning process is still considered difficult by students. Also, the Arabic language learning process still feels monotonous for students. This study aims to improve the mufrodat learning outcomes of 8th-grade students of Mts Minhajul Haq in Arabic Language Subjects using Crossword media (al-kalimat al-mutaqothi'ah). The method used by researchers is the classroom action research method (PTK) with data collection techniques through observation, tests, and field notes. The results of this study indicate that Crossword media (TTS) can improve students' mufrodat learning outcomes in Arabic language learning in class VIII Mts Minhajul Haq Purwakarta. This can be seen from the average pretest results of 58.67, then the average results of Mts Minhajul Haq students have increased from the posttest results to 89.65. Thus this Crossword media can be an alternative solution for Arabic language teachers because Crossword has characteristics including; fun, easy, provides challenges for students, and adds curiosity to students to find answers.